VAD Regimen as Initial Treatment for Multiple Myeloma - Mohammad Ali Mashhadi; Mehdi Hashemi; Negin Khosravi (International Journal of Hematology-Oncology and Stem Cell Research, 2010)
"nIntroduction: The aim of our study is evaluation of response rate of VAD (Vincristin, Adriamycin and Dexamethason) regimen as initial treatment in 40 new cases of multiple myeloma. This is the first systemic and classic report of VAD regimen in Iranian population. "nMethods: All patients with at least stage 2 multiple myeloma or progressive disease after physical examination, para- clinical profile such as (Imaging, CBC, BUN, Creatinine, Ca, P, Alk Phos, protein eletrophoresis, immuno electrophoresis and B2 Microglobuline) entered to this study and investigation. All patients received VAD regimen (Vincristin 0.4mg/day 1-→4 days, Adriamycin 9mg/m2 1-→4 days and Dexamethasone 40 mg/day/1→4 (days), 9→12 (days), 17→20 (days)/cycle in outpatient therapy (24mg/morning and 16 mg evening) and repeated every 28 days for 4 cycles. The evaluation of response rate was with: decreased clinical manifestation, changes in para clinical profile and M- component and B2 microglubuline. "nResults: Fourty (40) patients enrolled, 24 cases (60%) were female, 16 (40%) male, the mean age was 48 (25- 64), IgG myeloma was 80% (32), IgA myeloma 15% (6), and IgM myeloma 5% (2). 9 cases had thrombocytopenia in initiation of treatment and 7 cases during treatment protocol, and in the end of treatment, thrombocytopenia remained in 3 cases (total 16 cases) with mild thrombocytopenia (PLT= 100,000- 120,000), azotemia detected in 7 cases and in 2 cases resolved during treatment protocol. The over all response rate was 85%, median survival to now was 44.3 months. Toxicity was mild and acceptable. "nConclusion: Our result revealed the high response rate of VAD regimen as initial therapy and good survival rate with minor and acceptable toxicity.